Experimental and theoretical (ReaxFF) study of manganese-based catalysts for low-temperature toluene oxidation. Issue 3 (1st February 2021) - Duplančić, Marina; Gomzi, Vjeran; Pintar, Albin; Kurajica, Stanislav; Tomašić, Vesna
Abstract: This study presents detailed experimental and theoretical investigation of manganese-based metal oxides, MnMOx (M: Fe, Ni, Cu) as potential catalysts for the low-temperature toluene oxidation. The first part of the paper deals with the detailed characterization of the prepared catalysts and testing of their catalytic activity and stability in the fixed-bed reactor. The MnFeOx exhibited superior and stable catalytic activity for toluene oxidation (T90 = 419–446 K), comparable with the activity of the commercial Pt–Al2 O3 catalyst (T90 = 393–423 K). Among the studied catalysts the following order of catalytic activity was determined: MnFeOx > MnNiOx ≈ MnCuOx > MnOx . The one-dimensional (1D) pseudo-homogeneous model was applied to describe behavior of the fixed bed reactor for the low temperature toluene oxidation over prepared MnFeOx catalysts. The second part of the paper is focused on theoretical investigation of toluene interaction on the surface of the single metal oxides (Mn2 O3, MnO2, Fe2 O3, NiO and CuO) in the oxygen atmosphere using the ReaxFF method, since they were individual dominant phases in the prepared catalysts. A good correlation between the predicted binding energy of toluene adsorption on the surface of studied metal oxide phases and experimentally determined catalytic activities was observed.